2012
DOI: 10.1007/s00330-012-2440-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of digital tomosynthesis on the radiological investigation of patients with suspected pulmonary lesions on chest radiography

Abstract: DTS avoided the need for CT in about three-quarters of patients with a slight increase in the interpretation time and effective dose compared to CXR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 23 publications
4
48
0
5
Order By: Relevance
“…It included prospective evaluation of all nodules (with CT confirmation) in eligible subjects rather than just suspected nodules noted on conventional chest radiographs (18,21), and it therefore reflects the type and range of nodules encountered clinically, including those not visible on conventional chest radiographs. In this study, radiologist readers were also used from a wider range of specialty training than those in many previously published reports in which trained thoracic radiologists were predominantly used (11,12,(15)(16)(17)(18)20,21,48,49). Analysis of the effect of reader experience by using the most sensitive measure (weighted JAFROC FOM) showed that there was no significant difference between the performance of the thoracic and nonthoracic radiologists for any of the individual modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It included prospective evaluation of all nodules (with CT confirmation) in eligible subjects rather than just suspected nodules noted on conventional chest radiographs (18,21), and it therefore reflects the type and range of nodules encountered clinically, including those not visible on conventional chest radiographs. In this study, radiologist readers were also used from a wider range of specialty training than those in many previously published reports in which trained thoracic radiologists were predominantly used (11,12,(15)(16)(17)(18)20,21,48,49). Analysis of the effect of reader experience by using the most sensitive measure (weighted JAFROC FOM) showed that there was no significant difference between the performance of the thoracic and nonthoracic radiologists for any of the individual modalities.…”
Section: Discussionmentioning
confidence: 99%
“…igital tomosynthesis has been applied to a variety of applications, including breast imaging (1-3), orthopedic imaging (4-8), urologic imaging (9), and chest imaging (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Digital chest tomosynthesis has been available and cleared by the U.S. Food and Drug Administration since 2006.…”
mentioning
confidence: 99%
“…In the Table 1 SOS study, we showed that 6.5 × 10 −1 % of subjects had lung cancer, to be compared to a nearly 500 times lower risk of REID (0.3 × 10 −3 %) for the same pathology, suggesting that the screening procedure, even if expose the subjects to radiation, is advantageous. All the published studies [14,16,[26][27][28] on DTS report the sensitivity of DTS using CT as a reference, defining sensitivity as the ratio of number of nodules detected by DTS and CT. This is a direct consequence of the design of these studies that were conceived to test DTS on a population of subjects that already performed, for different reasons, a CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Although the estimated effective dose varied from 0.10 to 0.36 mSv in the past studies assessing GGN detectability by using CDT at reduced doses, 11,[26][27][28][29][30] CDT have demonstrated superiority in the GGN detectability to chest radiography even at an effective dose of 0.10-0.19 mSv; however, CDT has not yet achieved its comparability to LDCT at such doses. 31 Whereas, on CT images obtained at a similar dose to chest radiography (effective dose: 0.13-0.29 mSv), 21,31,32 beneficial effects of IR on image noise reduction and comparability in GGN detectability to LDCT have been shown.…”
Section: Discussionmentioning
confidence: 99%